Impact of home-based training and nutritional behavior on body composition and metabolic markers in cancer patients: data from the CRBP-TS study - Darmochwal, Sophia; Bischoff, Christian; Thieme, René; Gockel, Ines; Tegtbur, Uwe; Hillemanns, Peter; Schulze, Antina; Voss, Johannes; Falz, Roberto; Busse, Martin (Frontiers in Nutrition, 2023)
Obesity and physical inactivity are known to affect cancer's development and prognosis. In this context, physical aerobic and resistance training as well as a Mediterranean nutrition have been proven to have many positive health effects. The aim of this study was therefore to investigate the effect of home-based training on body composition and certain metabolic laboratory parameters.Patients with breast, colorectal and prostate cancer who underwent curative surgery at stages T1N0M0 to T3N3M0 were eligible for this trial and randomized to an intervention and control group. In the intervention group the patients carried out online-based strength-endurance home training during the 6-month study period.Body composition was assessed via bioelectrical impedance analysis (baseline, 3 months and 6 months). Metabolic blood parameters were also analyzed and nutrition behavior determined using the Mediterranean Diet Adherence Screener (MEDAS).The intervention group's fat mass decreased while their lean body mass increased (time effect (p=0.001 and p=0.001, respectively). We found no interaction effect in body weight (p=0.19), fat mass (p=0.06, 6-months estimates -0.9 [95% CI -1.8 to -0.1]) and fat-freelean body mass (p=0.9288). Blood samples also failed to show a statistically significant interaction effect between time x group for HbA1c% (p=0.64), Insulin (p=0.3391), Adiponectin (p=0.87), Leptin (p=0.52) and Triglycerides (p=0.43).Only Adiponectin revealed significance in the time effect (p<=0.00102) and Leptin in the group effect (p=0.03). Dietary behavior during the study period was similar in patients in the intervention and control groups (interaction p=0.81; group p=0.09 and time p=0.03).